South Africa: Social Accounting Matrix (SAM), 1993, 1998, and 1999 - Thurlow, James; van Seventer, Dirk Ernst (International Food Policy Research Institute, 2002)
The 1993, 1998, and 1999 SAMs for South Africa were constructed with the intention of incorporating the recently released supply-use tables for the country for these years. In line with this database, the SAM distinguishes between 43 productive sectors (activities) and the 43 commodities that they produce. By making use of the supply-use table, the SAM reflects how producers can produce more than a single commodity, and conversely, how a single commodity can be produced by more than a single producer. Therefore the SAM is a notable extension on existing SAMs for the country. The SAM accounts for four factors of production. These include unskilled, semi-skilled, and skilled labor, as well as the production factor capital. The SAM contains 14 representative households disaggregated across income deciles (with the exception of the top income decile, which is further subdivided into five income categories). Other institutions contained in the SAM include the rest of the world, the government, enterprises, and the savings-investment account.; For a description of the construction and use of the 1998 dataset, download the Trade and Macroeconomics Division Discussion Paper Number 100: (PDF 363K); Although there is no description of the construction of either the 1993 or the 1999 SAM, both use the same structure and data sources as the 1998 SAM for South Africa.